Improvement of endurance degradation for oxide based resistive switching memory devices correlated with oxygen vacancy accumulation effect - Gao, Bin (2013)
We report that the endurance degradation behaviors of transitional metal oxide (TMO) based resistive random access memory (RRAM) is dominated by three different steps and correlated with extra oxygen vacancy accumulation during SET/RESET switching process. The physical origin of endurance degradation due to the pulse voltage effect is verified by the measured data. The optimized operation schemes are accordingly proposed and implemented to enhance the endurance behavior. More than 108 switching cycles are achieved in the TiN/HfOx/TiOx structured devices.